Mastering iOS development : media library (Infinite Skills, 2014)
"In this iOS Media Library training course, expert author Keith Welch teaches you how to work with the various media options available in the iOS media library. You will start by learning about the image gallery in the media library. Keith will teach you how to take a picture using the camera and how to share the photo. You will learn how to record audio and video, as well as play audio and video files. This video tutorial also covers the PhotoKit gallery and how to create PhotoKit effects. Finally, this video tutorial will show you how to access the media library. By the completion of this computer based training course, you will be able to navigate and work within the iOS media library. Working files are included, allowing you to follow along with the author throughout the lessons. "--Resource description page.